Decolorization of Vat Violet 1 Dye from Textile Industrial Wastewater using Biofilm of Fungal and Bacterial Consortium - Lestari Wevriandini (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2019)
Increasing of textile industries creates a critical need for a proper treatment plan to control and minimize possibilities of contaminants and toxic compounds being released to the environment. Biological approaches by utilizing microorganisms, although because in the rise of practicality and cost-effectiveness, are still flawed and require more analysis and development. One of such approach that is often being researched is the utilization of biofilm for treating industrial waste, and among those is about the use of fungal and bacterial consortium. This research was conducted to examine and acquire a more stable biofilm formed by fungal and bacterial consortium for decolorization process of textile wastewater. Isolates were selected by examining their decolorization capability, antagonistic activity, and mixed culture formation (consortium). The selection continued with biofilm forming in material plastic LLDPE. Superior consortium from bacteria and fungi in the form of biofilm in material plastic LLDPE then was applied for the decolorization of Vat Violet 1 dye from textile industrial wastewater. The selection resulted in twosuperior fungal isolates coded as strain JYGC1 and K2; and three bacterial isolates were coded as strain ATA6, PK29, and PK65. These isolates were then combined to form biofilm on the surface of material plastic LLDPE and examined for their applicability to decolorize wastewater containing Vat Violet 1 under variation of pH condition of 5, 7, and 8. Biofilm with regular thickness was formed by the fungal bacterial consortium and capable of increasing the rate of decolorization activity. The highest biomass yield before and after application to the wastewater was found to be at pH 7 at about 0.66 g and 0.45 g, respectively. The thickness and biomass corresponds with decolorization activity, which is also the highest on pH 7, with difference of 1.155 between before and after application; much higher than without biofilm application at 0.714.